Physicochemical Evaluation of Chicken Liver Nuggets with Red Bean Flour (Phaseolus vulgaris L.) Substitution - Carneli, Resifa Yuni; Amertaningtyas, Dedes; Dellani, Christbugi Welda; Azkarahman, Aldyon Restu (Jurnal Ilmu dan Teknologi Hasil Ternak, 2026)
This study aims to determine the effect of substituting tapioca flour with red bean flour in chicken liver nuggets in terms of protein content, fat content, water activity, and moisture content. The main ingredients used are fresh chicken liver with tapioca flour and red bean flour as the substitute ingredients. This study used a laboratory experimental method with a completely randomized design (CRD) consisting of 5 treatments and 4 replicates. The treatments were T0 (100% tapioca flour as control), T1 (75% tapioca flour + 25% red bean flour), T2 (50% tapioca flour + 50% red bean flour), T3 (25% tapioca flour + 75% red bean flour), and T4 (100% red bean flour). The results showed that the substitution of tapioca flour with red bean flour in chicken liver nuggets showed a significant difference (p < 0.05) in protein content (11.16-12.84%), a highly significant difference (p < 0.01) in fat content (23.14-31.11%), and water activity (0.74-0.82), and no significant effect (p > 0.05) on moisture content (46.99-48.75%). It can be concluded that substituting tapioca flour with red bean flour in chicken liver nuggets produced the best results in treatment T4 (100% red bean flour), as indicated by the highest NH value and supported by improved physicochemical properties, including higher protein and fat content, as well as acceptable water activity and moisture content.